2007
DOI: 10.1158/0008-5472.can-07-0967
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Estrogen Receptor α Turnover and Transactivation by Mdm2 and Stress-Inducing Agents

Abstract: In mammalian cells, the level of estrogen receptor A (ERA) is rapidly decreased upon estrogen treatment, and this regulation involves proteasome degradation. Using different approaches, we showed that the Mdm2 oncogenic ubiquitinligase directly interacts with ERA in a ternary complex with p53 and is involved in the regulation of ERA turnover (both in the absence or presence of estrogens). Several lines of evidence indicated that this effect of Mdm2 required its ubiquitin-ligase activity and involved the ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 59 publications
6
92
0
Order By: Relevance
“…Among candidates whose siRNA-mediated depletion stabilizes HPIP, MDM2 was selected for further investigation given the previously established link between MDM2 and estrogen signaling (Figure 5a). 34 We confirmed that HPIP is indeed stabilized in the parental MCF7 cells infected with five distinct MDM2 shRNA lentiviral constructs (Figure 5b). HPIP and MDM2 protein levels were also inversely correlated in p53-depleted cells, indicating that MDM2 negatively regulates HPIP levels in a p53-independent manner.…”
Section: Tbk1 and Hpip Regulate Estrogen-mediated Akt Activationsupporting
confidence: 68%
See 1 more Smart Citation
“…Among candidates whose siRNA-mediated depletion stabilizes HPIP, MDM2 was selected for further investigation given the previously established link between MDM2 and estrogen signaling (Figure 5a). 34 We confirmed that HPIP is indeed stabilized in the parental MCF7 cells infected with five distinct MDM2 shRNA lentiviral constructs (Figure 5b). HPIP and MDM2 protein levels were also inversely correlated in p53-depleted cells, indicating that MDM2 negatively regulates HPIP levels in a p53-independent manner.…”
Section: Tbk1 and Hpip Regulate Estrogen-mediated Akt Activationsupporting
confidence: 68%
“…Therefore, MDM2 promotes E2-dependent AKT activation in p53-depleted breast cancer cells and is also involved in ERa turnover, as previously suggested. 34 Importantly, MDM2 depletion in p53-deficient MCF7 cells strongly sensitized them to tamoxifen, most likely as a result of defective AKT activation (Figure 7c). Although E2 stimulation triggered cell proliferation in p53-depleted MCF7 cells, as judged by the accumulation of cells in the S phase (from 11.1% in unstimulated cells to 23.7%), MDM2 deficiency severely impaired cell proliferation in both unstimulated and E2-treated cells (5.5% and 9.2%, respectively, see Figure 7d).…”
Section: Tbk1 and Hpip Regulate Estrogen-mediated Akt Activationmentioning
confidence: 96%
“…This phenomenon may be linked to (1) previous reports that the MDM2 GG genotype leads to high MDM2 protein expression (Bond et al,2004) and (2) the ability of MDM2 to negatively regulate estrogen receptor (ER) expression (Duong et al, 2007) because the estrogen signaling pathway is thought to be associated with an increased risk of developing lung cancer, especially adenocarcinoma (Karlsson et al, 2012). In addition, polycyclic aromatic hydrocarbons, which are important component of both cooking oil fumes and cigarette smoke, are reported to decrease estrogen levels (Siegfried, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2). Mdm2 can physically interact with ligand-binding domain of ERα regardless of the presence of estrogen and can directly enhance ERα ubiquitination in vivo [160]. Mdm2 oncogenic ubiquitin-ligase directly interacts with ERα in a ternary complex with p53 and is involved in the regulation of ERα turnover (both in the absence or presence of estrogens).…”
Section: Sumoylation Of Estrogen Receptormentioning
confidence: 99%